The effectiveness of health education using video media and leaflets on the ability to mobilize early in post caesarean section patients - Kusumawati, Ely; Hartati, Dwi; Astutik, Widya; Meihartati, Tuti (Institute of Computer Science (IOCS), 2024)
Early mobilization helps speed up post-surgical recovery, allowing wound healing and improving blood circulation. Post-caesarean section, the patient is at Dr Abdul Rivai Hospital Berau; after 6 hours post-caesarean section is still afraid of early mobilization and needs to learn more about early mobilization. A lack of early mobilization ability can be a lack of information, which creates a lack of motivation. Health education is carried out by hospitals through counseling, without using media such as videos and leaflets. Purpose: This study aimed to know the effectiveness of health education using video media and pamphlets on the ability of early mobilization in Post Sectio Caesaria patients. This was a quasi-experimental research type with two pre- and post-test design groups. The population was post sectio caesarea patients at dr. Abdul Rivai Hospital Berau in September 2023 numbered 81 people, based on the Lameshow formula, a sample of 30 people, including video and leaflet media groups of 15 people each. The early mobilization score before giving video media was a mean value of 5.67, and after giving video media, a mean value of 7.53. The early mobilization score before providing the leaflet media was a mean value of 5.67, and after providing the leaflet media, the mean value was 7.27. It showed differences in the effectiveness of health education using video and leaflet media on early mobilization abilities. This indicates that Video media and leaflets can help improve early mobilization abilities in Post Sectio Caesarea patients.